IMPROVING PROBLEM SOLVING ABILITY THROUGH THE IMPLEMENTATION OF PROBLEM-BASED LEARNING ASSISTED BY SQUARE PUZZLE MEDIA - Fitriana Mahmudah; Henry Suryo Bintoro; Deka Setiawan (JURNAL PAJAR (Pendidikan dan Pengajaran), 2020)
The aim of this classroom action research was to improve problem solving skills of the fourth grade students at Sekolah Dasar Negeri 2 Lambangan through the implementation of Problem-Based Learning model assisted by square puzzle media. This research involved 19 students as the subjects. This research was conducted in 2 cycles; each cycle consisted of 4 stages: planning, action, observation, and reflection. The independent variable in this study was a Problem-Based Learning model assisted by the square puzzle media. After that, the dependent variable was problem solving abilities. Data were collected through interviews and tests. The interviews were carried out to determine students’ interest in learning mathematics while the test was carried out to measure students’ mathematical problem solving abilities. Then, the data were analyzed quantitatively. The results showed that there was an increase on problem solving abilities in cycles I and II. The percentage of classical learning completeness increased from 63.15%, in cycle I, to 84.21%, in cycle II. The increase in problem solving abilities was caused by the implementation of Problem-Based Learning model which was student-centered. This model encouraged students to take an active role in problem solving activities. Besides, it was also supported by the use of square puzzle media which made it easier for students to build their understanding towards the materials about circumference and area of a two-dimentional figures (square and rectangle).